Minecraft beginner's guide : start your survival and creative journeys (Random House Worlds, 2024)
Helps newbies become immersed in Minecraft, a sandbox game set in a blocky, three-dimensional world, whether it be in Survival or Creative mode, by joining book guides Mis Hap, Sir Vival and Bill Ding on an adventure through the Overworld.